IMPLEMENTASI PENDEKATANLEAN SIX SIGMAUNTUK PENINGKATAN MUTU LULUSAN (STUDI PADA PPS. MMP UKSW SALATIGA) - Tijow, Meylani Aljeinie; Supramono, Supramono (Universitas Kristen Satya Wacana, 2015)
The main purpose of the implementation of Lean Six Sigma in this study is to improve the graduatesâ quality of PPs. MMP UKSW. Although PPs. MMP UKSW hasÂ an A accreditation, there are some graduates that graduated through a long studyÂ period that exceed the ideal standart. The method that used is DMAIC methodologyÂ (Define, Measure, Analyze, Improvement, Control) with the quality indicator based onÂ accreditation assessment of master degree. The data is collected by FGD (Focus GroupÂ Discussion) and analyzed by fishbone diagram and 5Whys. The result showed thatÂ beside the length of study period, the main problem of graduatesâ quality of PPs. MMPÂ UKSW is the lack of alumnisâ participation. The root problem of study period is focusedÂ on how the student are wasting the time to wait writing the proposal or thesis, while theÂ root problems for alumnisâ participation is because of their busy job. Based on those findings, there are 7 strategies for institution to improve the quality of graduates.